Development and evaluation of curcumin nano-niosomes for glioma-targeted therapy - Hao Qian; Jiaqi Lv; Xiuping Hu (Scientific Reports)
Abstract Glioma remains a significant global health challenge, and is characterized by a persistently high mortality rate. Chemotherapy is a common treatment for glioma, but many anticancer drugs exhibit poor permeability across the blood–brain barrier (BBB) and fail to reach tumor tissues adequately, while also exerting toxic effects on normal cells. To address these issues, this study investigated the use of niosomes (Nio), which are biocompatible, biodegradable, and non-immunogenic, to encapsulate curcumin (Cur) and enhance its delivery to glioma tissues. Niosomes were prepared using the non-ionic surfactant sorbitan monostearate (Span 60) and cholesterol as carrier materials, and subsequently modified with transferrin (TF) to facilitate receptor-mediated transport across the BBB. The resulting TF-modified curcumin niosomes (TF-Cur-Nio) demonstrated enhanced targeting of brain tumors, improved anti-glioma efficacy, and favorable in vivo safety. These findings suggest that the TF-Cur-Nio delivery system has significant potential for advancing glioma treatment by overcoming the limitations of conventional chemotherapy and improving drug delivery to the brain.